The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0167614
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature-Induced Defects in Tomato (Solanum lycopersicum) Anther and Pollen Development Are Associated with Reduced Expression of B-Class Floral Patterning Genes

Abstract: Sexual reproduction is a critical process in the life-cycle of plants and very sensitive to environmental perturbations. To better understand the effect of high temperature on plant reproduction, we cultivated tomato (Solanum lycopersicum) plants in continuous mild heat. Under this condition we observed a simultaneous reduction in pollen viability and appearance of anthers with pistil-like structures, while in a more thermotolerant genotype, both traits were improved. Ectopic expression of two pistil-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 58 publications
0
25
0
1
Order By: Relevance
“…Both extreme temperatures and prolonged periods of moderately elevated temperatures can impact different plant activities leading to reductions in fruit set or fruit yield (Mesihovic et al, 2016). Different tomato plant cultivars growing under chronic mild heat stress showed that pollen release, pollen viability, and anther morphology were major limiting factors for optimum fruit set (Sato et al, 2000;Müller et al, 2016;Xu et al, 2017). One of the main biochemical parameters that influenced pollen viability and development of young tomato fruits during heat stress periods was an optimal carbohydrate metabolism (Pressman et al, 2002;Firon et al, 2006;Li et al, 2012;Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Both extreme temperatures and prolonged periods of moderately elevated temperatures can impact different plant activities leading to reductions in fruit set or fruit yield (Mesihovic et al, 2016). Different tomato plant cultivars growing under chronic mild heat stress showed that pollen release, pollen viability, and anther morphology were major limiting factors for optimum fruit set (Sato et al, 2000;Müller et al, 2016;Xu et al, 2017). One of the main biochemical parameters that influenced pollen viability and development of young tomato fruits during heat stress periods was an optimal carbohydrate metabolism (Pressman et al, 2002;Firon et al, 2006;Li et al, 2012;Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Such divergent results may be related to the different genotypes used in the crosses of both works or, still, to environmental factors. According to Müller et al (2016), sexual reproduction is very sensitive to environmental perturbations, and pollen viability can vary accordingly under high temperature and in thermotolerant genotypes, as observed for cultivated tomato (Solanum lycopersicum).…”
Section: Discussionmentioning
confidence: 99%
“…Studies to define HS-related processes frequently make use of tomato (Solanum lycopersicum L.), which in addition to serving as model for HSR is an important crop [17,21,22]. On the one hand, the thermotolerance mechanisms in tomato have been examined at molecular, physiological and genetic levels and the results have fueled basic models describing the regulation of HSR in plants [23,24].…”
Section: Introductionmentioning
confidence: 99%